A performance evaluation of ARM ISA extension for elliptic curve cryptography over binary finite fields - Bartolini, S.; Branovic, I.; Giorgi, R.; Martinelli, E. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
In this paper, we present an evaluation of possible ARM instruction set extension for elliptic curve cryptography (ECC) over binary finite fields GF(2/sup m/). The use of elliptic curve cryptography is becoming common in embedded domain, where its reduced key size at a security level equivalent to standard public-key methods (such as RSA) allows for power consumption savings and more efficient operation. ARM processor was selected because it is widely used for embedded system applications. We developed an ECC benchmark set with three widely used public-key algorithms: Diffie-Hellman for key exchange, digital signature algorithm, as well as El-Gamal method for encryption/decryption. We analyzed the major bottlenecks at function level and evaluated the performance improvement, when we introduce some simple architectural support in the ARM ISA. Results of our experiments show that the use of a word-level multiplication instruction over binary field allows for an average 33% reduction of the total number of dynamically executed instructions, while execution time improves by the same amount when projective coordinates are used.